DERIVATOGRAPHIC ANALYSIS OF NAVBAHOR BENTONITE IN NANOCATALIZATOR TECHNOLOGY (American Journal of Interdisciplinary Research and Development, 2022)
In this study, the study of drying process using convektiv-UYuCh EMC energy in obtaining nanocatalyser from" Navahor " bentonite was covered. Also, the relevance of the topic, the experimental device of the laboratory used in the study, the research techniques and the analysis of the results obtained are presented. On the basis of the purpose of the work, the study of the drying process in the technology of obtaining a nanocatalizer and the acceleration of the process and technology by carrying it out in UYuCh EMC, the quality of texturized descriptions of loyi samples of "Navakhor" bentonite (catalyst)has been achieved.